In Situ Accessibility of Escherichia coli 23S rRNA to Fluorescently Labeled Oligonucleotide Probes - Fuchs, Bernhard M. (American Society for Microbiology, 2001)
One of the main causes of failure of fluorescence in situ hybridization with rRNA-targeted oligonucleotides, besides low cellular ribosome content and impermeability of cell walls, is the inaccessibility of probe target sites due to higher-order structure of the ribosome. Analogous to a study on the 16S rRNA (B. M. Fuchs, G. Wallner, W. Beisker, I. Schwippl, W. Ludwig, and R. Amann, Appl. Environ. Microbiol. 64:4973–4982, 1998), the accessibility of the 23S rRNA of Escherichia coli DSM 30083(T) was studied in detail with a set of 184 CY3-labeled oligonucleotide probes. The probe-conferred fluorescence was quantified flow cytometrically. The brightest signal resulted from probe 23S-2018, complementary to positions 2018 to 2035. The distribution of probe-conferred cell fluorescence in six arbitrarily set brightness classes (classes I to VI, 100 to 81%, 80 to 61%, 60 to 41%, 40 to 21%, 20 to 6%, and 5 to 0% of the brightness of 23S-2018, respectively) was as follows: class I, 3%; class II, 21%; class III, 35%; class IV, 18%; class V, 16%; and class VI, 7%. A fine-resolution analysis of selected areas confirmed steep changes in accessibility on the 23S RNA to oligonucleotide probes. This is similar to the situation for the 16S rRNA. Indeed, no significant differences were found between the hybridization of oligonucleotide probes to 16S and 23S rRNA. Interestingly, indications were obtained of an effect of the type of fluorescent dye coupled to a probe on in situ accessibility. The results were translated into an accessibility map for the 23S rRNA of E. coli, which may be extrapolated to other bacteria. Thereby, it may contribute to a better exploitation of the high potential of the 23S rRNA for identification of bacteria in the future.